(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Urbanization and population growth at a fast pace are indeed the biggest challenges in municipal waste management for developing countries like India. Cities like Raipur, Rudrapur, and Bilaspur are feeling a growing pressure to establish effective, sustainable, and inclusive waste management systems so that public health, environmental, and economic concerns could be properly addressed. This study aims at evaluating challenges, economic opportunities, and potential improvements in SWM with an emphasis on public engagement, willingness to pay for improved services, and the integration of waste-to-energy (WTE) technologies. Auxiliary industries were also analyzed in promoting sustainable solutions to waste management.